Nasal cavity myiasis presenting with preseptal cellulitis - Singh, Kelvinder; Prepageran, Narayanan; Mohd Nor, Khadijah (Taylor and Francis, 2017)
Nasal Myiasis is the infestation of the nasal cavity by dipterous larvae and which are commonly documented in developing countries where sanitation is a public problem. Other predisposing factors being poorly nourished patient with poor hygiene, atrophic rhinitis, and diabetic with purulent nasal discharge, midline granulomatous lesions or malignancy involving the nose. We have reported a case of a patient with underlying sinonasal tumour post excision and postoperative concurrent chemoradiation presenting with preseptal cellulitis and nasal myiasis.